Psychological distress and quality of life following positive fecal occult blood testing in colorectal cancer screening. Issue 6 (14th April 2020) - Vermeer, Nina C. A.; van der Valk, Maxime J. M.; Snijders, Heleen S.; Vasen, Hans F. A.; Gerritsen van der Hoop, Arthur; Guicherit, Onno R.; Liefers, Gerrit‐Jan; van de Velde, Cornelis J. H.; Stiggelbout, Anne M.; Peeters, Koen C. M. J.
Abstract: Objective: This study aimed to assess psychological functioning, quality of life, and regret about screening after a positive fecal immunochemical test (FIT) and subsequent colonoscopy, and to evaluate changes over time. Methods: This is a prospective cohort study. Individuals aged 55 to 75 with a positive FIT that were referred for colonoscopy between July 2017 and November 2018, were invited to complete questionnaires related to psychological distress and health‐related quality of life at three predefined time points: before colonoscopy, after histopathology result notification, and after 6 months. Four questionnaires were used: the Psychological Consequences Questionnaire (PCQ), the six‐item Cancer Worry Scale (CWS), the Decision Regret Scale (DRS), and the 36‐item Short‐Form (SF‐36). Results: A total of 1066 participants out of 2151 eligible individuals were included. Patients with cancer showed a significant increase in psychological dysfunction ( P = .01) and cancer worry ( P = .008) after colonoscopy result notification, and a decline to pre‐colonoscopy measurements after 6 months. In the no‐cancer groups, psychological dysfunction and cancer worry significantly decreased over time ( P < .05) but there was no ongoing decline. After 6 months, 17% of participants with no cancer experienced high level of cancer worry (CWS ≥ 10). Yet, only 5% reported high level of regret about screening participation (DRS > 25). A good global quality of life was reported in participants with no cancer. Conclusion: Some psychological distress remains up to 6 months after colonoscopy in participants who tested false‐positive in the Dutch bowel cancer screening program.